Modernity Growth and Heritage Design in UAE - Рей, Амер (Рroblems of engineering and professional education, 2023)
In the Middle East, there are many valuable heritage sites that provide great potential for linking the past region with present and future. Despite of globalization, the environment can be still considered significant and relevant in the Middle East and many other regions of the world, especially in countries with less technological and economic resources. Madinat Jumeirah is a real and significant stylistic task for the whole urban landscape of modern Dubai. The task is an example of the traditional urban features of Dubai in the new urban design scene.